On the question of innovations in the legal regulation of special principles of international civil procedure - Ramanava, Olga N. (Journal of the Belarusian State University. Law, 2026)
The article analyses the amendments to the Code of Civil Procedure of the Republic of Belarus concerning the system of special principles of international civil procedure (Art. 504). The enshrinement of the principle of the primacy of generally recognised principles of international law as a special principle of international civil procedure is critically assessed.
Keywords: international civil procedure; principles of international civil procedure; priority of generally recognised principles of international law; principle of priority of international treaties